Experiments on Single-Phase Nanofluid Heat Transfer Mechanisms in Microchannel Heat Sinks: A Review - Pinar Eneren; Yunus Tansu Aksoy; Maria Rosaria Vetrano (Energies, 2022)
For more than 20 years, the use of nanofluids to enhance heat transfer in microchannel heat sinks (MCHSs) has been the subject of a large number of scientific articles. Despite the great potentialities reported in several works, the presence of controversial results and the lack of understanding of heat transfer enhancement mechanisms prevent further advancement in the use of nanofluids as coolants. This article reviews the scientific literature focused on several aspects of nanofluids that have a role in the heat transfer enhancement within the MCHSs: nanofluid stability, thermal conductivity, and particle clustering, as well as the particle–surface interactions, i.e., abrasion, erosion, and corrosion. We also include the most relevant works on the convective heat transfer and MCHSs operated with nanofluids in our review.